Associations Between Relative Viral Load at Diagnosis and Influenza A Symptoms and Recovery. (16th October 2020) - McKay, Brian; Ebell, Mark; Billings, Wesley Zane; Dale, Ariella Perry; Shen, Ye; Handel, Andreas
Abstract: Background: Rapid point-of-care polymerase chain reaction (PCR) diagnostic tests generally provide a qualitative result of positive or negative only. Additional information about the relative viral load could be calculated. Such quantitative information might be useful for making treatment decisions. Methods: We enrolled students at a university health center who presented with cough and 1 additional flu-like symptom from December 2016 to February 2017. Data were collected before, during, and 5 days after the clinic visit. All those enrolled in the study received a point-of-care PCR test (cobas Liat). For those patients that tested positive for influenza A, we investigated correlations between the relative viral load and measures of disease severity and recovery. Results: One hundred thirty-five students tested positive for influenza A. We found a positive correlation between viral load and body temperature. Time since symptom onset seemed to have a negative correlation but was not statistically significant. We did not find any correlations between viral load and overall symptom severity or outcomes related to recovery. Conclusions: Although we found a correlation between relative viral load and body temperature, for our study population of young, overall healthy adults, we did not find that relative viral load provided additional information that could help in determining treatment and disease outcomes. It could be that viral load does provide useful additional information for other groups of patients, such as young children or older adults. Further studies on those populations are warranted. Abstract : Rapid point-of-care (POC) PCR tests can generate estimates of viral load. Viral loads at diagnosis using a POC PCR test are associated with body temperature. Among our population, viral load at diagnosis was not predictive of disease severity or recovery.